Penerapan INLISlite (Integrated Library System) di Kantor Perpustakaan dan Arsip Daerah Kabupaten Pangkep, Sulawesi Selatan - Hamid, Abdul (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2015)
Information and communication technology (ICT) has been undoubtly applied in all fields of life. It provides variety of services in which it is dependent on user needs. The Kantor Perpustakaan dan Arsip Daerah (the District Library and Archieve of Pangkep) has been implementing ICT to enhance its services to the citizens of Pangkep. INSLISLite was choosen as its automted library system. The current study investigates how INLIS lite has been implemented in the library, what were the challanges the library faced, and the floating library services of KPAD. The data were collected throughout the representative informans. The study found that INLIS lite needed to be more optimized, the challenges were human resources and budgetary, and the floating library has played important roles to educate the Pangkep island citizens.